On convergence (2,1,…,1)-periodic branched continued fraction of the special form - Bodnar, D.I.; Bubniak, M.M. (Carpathian Mathematical Publications, 2015)
(2,1,…,1)-periodic branched continued fraction of the special form is defined. Conditions of convergence are established for 2-periodic continued fraction and (2,1,…,1)-periodic branched continued fraction of the special form. Truncation error bounds are estimated for these fractions under additional conditions.